A tough fluorescent nanocomposite hydrogel probe based on graphene quantum dots for the selective detection of Fe3+ ions. Issue 20 (12th August 2022) - Du, Juan; Zhu, Wenli; She, Xiaohong; Yu, Qiyu; Yang, Qiaoling; Huang, Huiping; Tsou, Chihui; Manuel, De Guzman
Abstract : A tough fluorescent nanocomposite hydrogel probe crosslinked by graphene quantum dots for the selective detection of Fe 3+ ions. Abstract : Herein, poly(acrylamide- co -acrylic acid)/GQD (poly(AM- co -AA)/GQD) nanocomposite hydrogels were prepared by in situ free radical polymerization using graphene quantum dots (GQDs) as a multifunctional crosslinker. The appropriate size and plenty of surface functional groups enabled GQDs to effectively adsorb large amounts of polymer chains and act as a multifunctional crosslinker in gels, thus forming a denser and more uniform crosslinked network in poly(AM- co -AA)/GQD nanocomposite hydrogels, and in turn endow the resultant nanocomposite hydrogel with excellent mechanical properties and self-healing properties. Compared to poly(AM- co -AA) hydrogels, about a 4.04-fold increase of tensile strength, a 4.51-fold increase of elongation at break and 1.06 times compressive strength compared to those of poly(AM- co -AA) hydrogels were achieved when the content of GQDs in poly(AM- co -AA)/GQD nanocomposite hydrogels was 1 wt%, suggesting that GQDs could effectively improve the mechanical properties of the hydrogels. Besides, GQDs could give poly(AM- co -AA)/GQD nanocomposite hydrogels excellent fluorescence, and a strong blue luminescence emission at a maximal peak at 459 nm when they were excited at 360 nm. Moreover, due to the fluorescence quenching of GQDs, the obtained poly(AM- co -AA)/GQD nanocomposite hydrogels were able to sense Fe 3+ ions. As a result, the nanocomposite hydrogels were selective to Fe 3+ ions, and the fluorescence intensity linearly responded to the Fe 3+ ion concentration in the range of 10–160 μmol L −1 ( R 2 = 0.9686). The fluorescence hydrogel can be used as an effective fluorescent probe for the detection of Fe 3+ ions in an aqueous solution in the future.